Family Planning According to the Lembaga Dakwah Islam Indonesia and Nahdlatul Ulama Bandar Lampung City - Muhammad Iqbal Abdussalam; Zezen Zainul Ali (Institut Agama Islam Negeri Kerinci, 2022)
This article discusses the views of the organizational figures of the Lembaga Dakwah Islam Indonesia (Indonesian Islamic Da'wah Organization) and the Nahdhatul Ulama of Bandar Lampung City regarding the Family Planning program whose laws are often debated by the general public. Those who think that the family planning program is legal can be based on government recommendations, while those who think that the law is prohibited are based on the views of certain religious groups or organizations. This study uses a qualitative-descriptive approach. Data were collected through interviews with organizational figures from the Indonesian Islamic Da'wah Institute and Nahdhatul Ulama in Bandar Lampung City. This study found that there is a tendency to prohibit or prohibit the Indonesian Islamic Da'wah Organization against the Family Planning program if the consideration is economic difficulties. However, for birth control, this organization offers the azl method known in Islamic fiqh. Meanwhile, Nahdhatul Ulama figures fully support the Family Planning program run by the government, because there is benefit and there is no element of conflict with Islamic law in principle.